Problems of psychological support of professional activity of the employees of the State Penitentiary Service of Ukraine - I. M. Okhrimenko (Law and Safety)
It has been noted that official activities of the employees of the State Penitentiary Service (SPS) of Ukraine is directly related to the presence of a significant number of stressful factors and requires the comprehensive use of psychological tools and technologies. This affects the efficiency of professional activities of the specialists within penitentiary sphere. Taking into account the special conditions of professional activity of the employees of the SPS of Ukraine, the author has distinguished the main directions of the system of psychological support of professional activity of the employees of the SPS of Ukraine.